El Excentrico, 1962-07-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
July 5, 1962 [5 de Julio de 1962]. Ano 12, No 17. Cover has photograph of Miss Lorie Reyes with headline "Lorie Reyes Queen candidate for 16th of Sept. Fiesta."